FEATURES OF DURABILITY CALCULATION FOR MACHINE PARTS AND STRUCTURAL ELEMENTS UNDER HIGH ASYMMETRIC LOW-AMPLITUDE LOAD CONDITIONS - Artym, V. I.; Faflei, O. Y.; Pents, V. F.; Kariuk, A. M. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The study has been conducted by means of physical, mathematical and computer modeling integrated method use. To prove the adequacy of the results obtained the experimental procedure on the existing equipment and laboratory facilities has been applied. The method of carrying out asymmetric stress cycles with mean stress of stretching to symmetric using the proposed piecewise – linear equations for evaluating the material sensitivity to asymmetry of the cycle has also been improved. It has enabled pipe column element durability under the condition of typical asymmetric low-amplitude loading calculation.
Keywords: stress reduction; the boundary toughness; the asymmetry of the cycle